Comparative Associations between Substances Used with Depression and Anxiety in a Sample of High School Students in Turkey - Unlu, Ali; Prajapati, Parna; Rahmani, Mariam; Pumariega, Andres (Adolescent Psychiatry, 2024)
Objective: To explore the associations between the type and the amount of substances used with depression and anxiety symptoms by high school students. Methods: The study data was collected by the Istanbul Department of Education on 31,604 high school students which was a survey of 66 questions administered in the school setting. The primary questions and sub-questions on anxiety and depression scores were added to generate a scaled score. Specific substances used by the participants were used to explore the relationship between substance use and depression and anxiety scores by using multinomial logistic regression models. Two regression models were analyzed, one for each dependent variable, keeping the significance level at 0.05. Odds ratios were calculated to explore the association between depression and anxiety scores and specific substance use among the youth. Results: The participants with low levels of anxiety were at an increased odds of using heavy amounts of sleep pills (OR=1.6) and alcohol (OR=1.3) as compared to those without anxiety. In addition to sleep pills and alcohol, illicit substances such as LSD and inhalant use were also seen in the participants with higher levels of anxiety. The participants with low levels of depression were found to be at an increased odds of using sleep pills (OR=1.8) and alcohol (OR=1.3). In addition to this pattern of substance use, participants with higher levels of depression were also found to be heavy cocaine users, low inhalant users, heavy steroid users, and low alcohol users. A decrease in the use of homemade brews was seen in the participants with low and high levels of depression as compared to those who didn't have any depressive symptoms. Conclusion: A unique pattern of drug and alcohol use was found in the participants experiencing varying levels of anxiety and depression.
Keywords: high school students